2012
DOI: 10.5505/tjb.2012.43434
|View full text |Cite
|
Sign up to set email alerts
|

Cellulase and xylanase production by co-culture of Aspergillus niger and Fusarium oxysporum utilizing forest waste

Abstract: Aim: The purpose of present work was to utilize lignocellulosic forest waste for cost-effective production of commercially important enzymes i.e. cellulase and xylanase by employing co-culture of Aspergillus niger F 7 and Fusarium oxysporum F 8 in solid state fermentation (SSF). Material and Methods: Fungal strains i.e. A. niger F 7 and F. oxysporum F 8 isolated from degrading forest litter were used as co-culture and their enzyme biosynthesis on forest waste was noticed. The prominent forest wastes i.e. Toona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 19 publications
(17 reference statements)
0
12
0
1
Order By: Relevance
“…Xylanases are also used in paper and pulp industries, textile and bioconversion of agricultural wastes into fermentative products [3]. Xylanases are normally produced using submerged fermentation, but solid-state fermentation has gained deep interest and attention of researchers due to its high percentage conversion rate biomass to energy conservation, agro-industrial waste treatment and in production of secondary metabolites [4]. In SSF process, the substrate in solid form not only provides the essential nutrients for the growth of microorganism in the culture but it also serves as a support for the microbial cells or body.…”
Section: Introductionmentioning
confidence: 99%
“…Xylanases are also used in paper and pulp industries, textile and bioconversion of agricultural wastes into fermentative products [3]. Xylanases are normally produced using submerged fermentation, but solid-state fermentation has gained deep interest and attention of researchers due to its high percentage conversion rate biomass to energy conservation, agro-industrial waste treatment and in production of secondary metabolites [4]. In SSF process, the substrate in solid form not only provides the essential nutrients for the growth of microorganism in the culture but it also serves as a support for the microbial cells or body.…”
Section: Introductionmentioning
confidence: 99%
“…The most common diseases caused by this species are keratitis, onychomycosis, and hyalohyphomycosis [36][37]. The less frequent occurrence of the genus Fusarium was identified also in other studies [2,15,38]. In the study on birch and spruce wood from Finland, the spores of genus Fusarium and Trichoderma were identified as well.…”
Section: Discussionmentioning
confidence: 84%
“…So, a greater enzyme production would be desirable in order to have a more eicient bioprocess. At this respect, it has been suggested that the cocultivation of microbes in fermentation can increase the quantity of the desirable components on a cellulose complex [27]. On the other side, some reports have shown that laccases or xylanases production can increase in a coculture mode, as happens with P. ostreatus, which increased ivefold its laccase production in a coculture with Trichoderma viride in submerged fermentation [28].…”
Section: Cocultures For Joint Production Of Lignocellulasesmentioning
confidence: 99%